Nurse Motivational Factors in Doing Restrain and Seclusion to the Client with Mental Disorder in Tampan Asylum in Pekanbaru 2015 - Erlin, F; Helena, N; Erwina, I (KnE Life Sciences, 2019)
Restrain and seclusion purpose is to take care of mental disorder client harshness behavior, in 2014 in PICU room of Tampan Asylum in Pekanbaru is considered high as 444 clients get 6 hours of restrain. The aim of the research is to identify the nurse motivational factors in doing restrain and seclusion to the client with mental disorder. The data collection used questionnaire which covered the physiological, security, care, pride and self-actualization fulfillment factor, also nurse motivation in doing restrain and seclusion. The population was 84 nurses with total sampling techniques, and the research was conducted in March - October 2015. The statistic analysis used Chi-square test. The result of univariate analysis shows nurse unsatisfactory of physiological fulfillment of 66,6 %, security is both satisfied and unsatisfied is same as 50%, unsatisfied care of 69%, unsatisfied pride of 72,6 %, unsatisfied actualization of 75% and high nurse motivation of 52,4% in doing restrain and seclusion. The result of bivariate analysis shows that there is a meaningful relation between the motivation in doing restrain and seclusion which is caused by factor of physiological need (p value=0,007), security (p value= 0,001), pride (p value= 0,017), while the factor of care need (p value= 0,173) and self-actualization (p value= 0,077) has no relation between the nurse motivation and doing restrain and seclusion. The research result become the information and evaluation in arranging the awareness policy of nursing standard, SOP of restrain and seclusion also sending the nurse for restrain and seclusion management training. Keywords: motivation, nurse and restrain, seclusion.